2011
DOI: 10.1007/s10897-011-9391-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Risk Information on Parental Role Identity in Adolescent Girls and Young Women from Families with Fragile X Syndrome

Abstract: Using a multi-group cross-sectional design, we explored self-concept related to parental role salience and enactment in 53 young women (14 to 24 years) with knowledge they were either carriers, non-carriers, or could be a carrier of fragile X syndrome (FXS). Parental role salience included the participants’ desire “to be a mother” and the importance they placed on this role. Enactment focused on the participants’ views regarding ways to become a mother (reproductive options), parenting a child affected by FXS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…A total of 45 studies met the inclusion criteria (Figure 1). A range of study designs were used, most of which were quantitative in nature (21 of 45 [47%]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 studies met the inclusion criteria (Figure 1). A range of study designs were used, most of which were quantitative in nature (21 of 45 [47%]).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative design was used in 12 additional studies (27%), and all 12 involved one-on-one interactions with participants; 8 of them also included semistructured interviews . The remaining 12 studies (27%) used knowledge synthesis (n = 4), case study (n = 4), or mixed methods (n = 4) design. Sample sizes (Table) ranged from 1 to 930, with a median of 23 and a mode of 9 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, before age 40, about 20% of female carriers develop fragile X premature ovarian insufficiency (FXPOI), which is characterized by decreased ovarian function and can lead to infertility and early menopause [52]. The associated estrogen deficits and potential feelings of reproductive inadequacy put them at increased risk for mood disorders [53,54]. Likewise, carriers with and without FXTAS have substantial rates of thyroid dysfunction, a known risk factor for mood and anxiety disorders [51].…”
Section: Neuropsychiatric Phenotypes In Adult Carriers Without Fxtasmentioning
confidence: 99%
“…Female fragile X carriers in one study may have actually demonstrated better coping mechanisms than untested girls who were aware that they were at risk (Wade et al 2010 ). Both carrier and non-carrier results can enable an adolescent to obtain a sense of control, potentially contributing to their personal growth and maturity (Järvinen et al 2000 ; McConkie-Rosell et al 2012 ). Furthermore, an unfavorable test result can reduce uncertainty, enabling an adolescent girl to adjust to the knowledge of her carrier status (Elger 2010 ; Fanos 1997 ).…”
Section: Introductionmentioning
confidence: 99%